The Influence of Motivation, Self-Efficacy, and Social Media Utilization on Business Interest Among Generation Z Students in the Business Administrasion Program at UPN “Veteran” Jawa Timur - Andri Rizal Setiawan; Acep Samsudin (International Journal of Social, Economic, and Business, 2025)
This study aims to identify and analyze the influence of Motivation, Self-Efficacy, and the Social Media Utilization on the Entrepreneurial Interest of Generation Z among Business Administration students at UPN "Veteran" East Java. This research applies a quantitative method with an associative approach. The data analysis technique used is multiple linear regression analysis, with a total sample of 76 students collected through direct questionnaires. The sample was selected using a non-probability sampling method with a saturated sampling technique. The research findings indicate that, simultaneously, Motivation, Self-Efficacy, and the Social Media Utilization have a positive and significant influence on the Entrepreneurial Interest of Generation Z among Business Administration students at UPN "Veteran" East Java. Partially,Motivation and Self-Efficacy have a positive and significant effect, while the Social Media Utilization does not significantly impact Entrepreneurial Interest. Based on these findings, the study program and university can implement more strategic policies to enhance the Entrepreneurial Interest of Generation Z students in Business Administration at UPN "Veteran" East Java. This study provides theoretical implications by expanding knowledge about the relationships between variables, as well as practical implications that can serve as a reference for universities in optimizing students' Entrepreneurial Interest.